The impact of processing and aging on the oxidative potential, molecular structure and dissolution of gelatin. (May 2017) - Duconseille, Anne; Traikia, Mounir; Lagrée, Marie; Jousse, Cyril; Pagès, Guilhem; Gatellier, Philippe; Astruc, Thierry; Santé-Lhoutellier, Véronique
Abstract: Gelatin is a biopolymer produced worldwide through its dissolution rate is variable. During the manufacturing process, gelatin is exposed to high temperatures known to be responsible for cross-link formation. Moreover, bleaching agents such as hydrogen peroxide are added to lighten the gelatin, leading to oxidation reactions that form cross-links. Cross-links have been reported in the literature to be formed between amino acids and related to decreased gelatin dissolution. The variability of gelatin dissolution is important since gelatin is used in the pharmaceutical industry to make hard capsules which have to satisfy strict dissolution specifications. The objective of this study was to determine how the oxidative potential of gelatin may explain the variability of its dissolution. Amino acid composition was assessed by HPLC and gelatin chemical composition was studied with HRMAS-NMR. Iron and aldehyde contents were also measured. Cross-links involving aldehyde functions were strongly suspected to be formed with aging, as were desmosine-like and dityrosine cross-links. All these cross-links were formed during oxidation reactions that are also strongly suspected to occur during aging. In addition, the origin of production affects the oxidative potential of gelatins when considering their iron content. The amount of aldehyde functions, which reflects the oxidation state of gelatins, differed as a function of their origin of production. The dissolution rate of gelatins could be linked to their oxidative potential (iron content) and the aldehydic products of lipid oxidation. Interestingly, the causes for differences in dissolution varied as a function of their origin of production. Graphical abstract: Highlights: Aldehyde functions are consumed during aging of gelatin. Desmosine & dityrosine are possibly be formed during aging under oxidation reaction. The origin of production of gelatin impacts the aldehyde and iron concentrations. Low dissolution gelatins exhibit higher iron content. Low dissolution gelatins have higher aldehyde concentration after aging.